Cardiovascular Dysfunction and Frailty Among Older Adults in the Community: The ARIC Study - Nadruz, Wilson (J Gerontol A Biol Sci Med Sci, 2017)
BACKGROUND: The contribution of cardiovascular dysfunction to frailty in older adults is uncertain. This study aimed to define the relationship between frailty and cardiovascular structure and function, and determine whether these associations are independent of coexisting abnormalities in other organ systems. METHODS: We studied 3,991 older adults (mean age 75.6±5.0 years; 59% female) from the Atherosclerosis Risk in Communities (ARIC) Study in whom the following six organ systems were uniformly assessed: cardiac (by echocardiography), vascular (by ankle-brachial-index and pulse-wave-velocity), pulmonary (by spirometry), renal (by estimated glomerular filtration rate), hematologic (by hemoglobin), and adipose (by body mass index and bioimpedance). Frailty was defined by the presence of ≥3 of the following: low strength, low energy, slowed motor performance, low physical activity, or unintentional weight loss. RESULTS: Two hundred eleven (5.3%) participants were frail. In multivariable analyses adjusted for demographics, diabetes, hypertension, and measures of other organ system function, frailty was independently and additively associated with left ventricular hypertrophy (odds ratio [OR] = 1.72; 95% confidence interval [CI] = 1.30–2.40), reduced global longitudinal strain (reflecting systolic function; OR = 1.68; 95% CI = 1.16–2.44), and greater left atrial volume index (reflecting diastolic function; OR = 1.60; 95% CI = 1.13–2.27), which together demonstrated the greatest association with frailty (OR = 2.10; 95% CI = 1.57–2.82) of the systems studied. Lower magnitude associations were observed for vascular and pulmonary abnormalities, anemia, and impaired renal function. Cardiovascular abnormalities remained associated with frailty after excluding participants with prevalent cardiovascular disease. CONCLUSIONS: Abnormalities of cardiac structure and function are independently associated with frailty, and together show the greatest association with frailty among the organ systems studied.